OPTIMALISASI LITERASI DAN EDUKASI DI PERPUSTAKAAN CERDAS, DESA BANJARNEGORO, MERTOYUDAN, MAGELANG - diesyana ajeng pramesti; Wheni Indi Astuti; Risalah Fatimatuz Zahra; Okfita Tri Susanti; Anggraeni Ratna Purnasiwi; Ninda Julia Tita Permana (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
Literacy and education in Cerdas Library, Banjarnegoro Village, Mertoyudan District, Magelang Regency has not been done optimally in the surrounding communities despite being Magelangs Regional library champion and having quite a complate book. With the cooperation of The District Library of Magelang and the dedication team of Muhammadiyah University Magelang, some bright ideas emarged to develop an intelligent and widely known library. These methods of activity in the service were used by a division of the 4 (four) stages of the survey, alization, appraisal, and monitoring of assessments. This activity take place for 3 (three) months. In this activity, it is introduced to online learning to communities, especially Elementary School children, through interesting games, fond socialization, library administration training for librarians, development training, and creative economics.